The Decision to Delist from the Stock Market Theory and Empirical Evidence of Going Private - Fidanza, Barbara (Springer International Publishing, 2018)
In an organized and organic way, this book covers all the possible theoretical and empirical facets of delisting, adding to the well-developed literature on IPOs. IPO and delisting are strictly related; the reasons for delisting may be found in the loss of the incentives that drove the firm to the public market in the past. However, the book presents unique motivations not directly related to the IPO decision. This book covers what the existing literature has not in focusing on specific aspects such as market liquidity and microstructure, listing costs, market for corporate control, corporate governance issues and so on. Of interest to academics and students, this contribution puts all pieces in order and finds a thread that can link each theory to the others.